(untitled) (Community Based Medical Journal, 2022)
Complete heart block (CHB) is a well-recognized complication in acute inferior myocardial infarction (MI) patients. A prospective observational study was conducted in the Coronary Care Unit (CCU) under Department of Cardiology, Sher-E-Bangla Medical College Hospital, Barisal, Bangladesh, from November 2014 to May 2015, to identify the risk factors and observe clinical prognosis and outcome in patients of acute inferior myocardial infarction associated with complete heart block. Convenient sampling technique was adopted and a total of 100 patients (77 males and 23 females) were selected based on specific inclusion and exclusion criteria. All the patients participated in the study were evaluated by detailed history, clinical examination and relevant investigations to identify the risk factors. ECG was done on daily basis and continuously observed. Response to treatment, complications and recovery of CHB were observed during hospital stay. The mean age of the patients was 57.16±10.24 years. Smoking (52%), dyslipidemia (36%), hypertension (31%) and diabetes mellitus (26%) were found most common risk factors among those patients. 71% of the patients had isolated inferior MI and was quite responsive to optimum medical therapy (92.95%) and mortality was low (2.81%). However, concomitant right ventricular infarction (18%), posterior infarction (4%) and anterior or lateral infarction/ischemia (7%) had a poorer outcome, i.e. 16.66%, 25%, and 57.14% death respectively. Early presentation (within 24 hours) of CHB had only 4.17% mortality. However, mortality increased in patients as CHB developed after 24 hours (26%). Overall, 10% mortality was observed even with advanced cardiac support. Our data suggest that smoking, dyslipidemia, hypertension and diabetes mellitus are most common risk factors of MI. Complete heart block complicating by acute inferior MI is very much responsive to optimum medical treatment and hardly requires temporary pacemaker. However, concomitant right ventricular infarction, posterior, anterior or lateral infarction/ ischaemia cause poor prognosis and increased mortality. CBMJ 2021 January: vol. 10 no. 01 P: 24-29